Financial distress in the banking industry: A bibliometric synthesis and exploration - Saib Fakhar; Fateh Mohd Khan; Mosab I. Tabash; Gayas Ahmad; Javaid Akhter; Mujeeb Saif Mohsen Al Absy (Cogent Economics & Finance, 2023)
Recent financial upheavals and economic downturns have triggered and sped up the research on financial distress in general and in the Banking industry in specific. The current review attempts to gauge and map performance trends and intellectual knowledge structure of the financial distress research in the banking industry. A hybrid approach was adopted to inventorize, analyse and evaluate the financial distress literature pertaining to the banking industry (1982-2022); the authors apply bibliometric analysis to identify critical financial distress literature articles and journals, followed by the identification of central financial distress literature research themes through co-citation analysis. We found that financial distress researchers have published 11 papers each year since 1982, and the number of citations received by the research domain has significantly risen, adding more importance to this research domain. Further, the analysis helps delineate four thematic knowledge clusters throwing light on the nomological network of the field and giving a bird's eye-view of the intellectual structure of the field. Since this review utilised data from a single database, i.e. Scopus, any shortcomings associated with the database would undoubtedly impact the results.
Keywords: 330; banking; bibliometrics; co-occurrence analysis; financial distress; systematic review